The Euro and the Production Structure and Export Performance of Middle East and North African Countries - Ruhashyankiko, Jean-Francois (IMF Working Papers; Working Paper ;, 1999)
This paper explores the link between exchange rate volatility of European currencies and economic performance of several countries in the Middle East and North Africa (MENA). The elimination of intra euro-zone exchange rate volatility resulting from the introduction of the euro is estimated to affect the production structure of MENA economies and shift their exports from manufacturing to agriculture and services. At the country and industry levels, the impact of the euro is more striking in countries with higher shares of manufacturing and higher shares of exports to the euro zone.